Religious Belief and Scientific Belief (American Journal of Islam and Society, 1994)
"Are those who know and those whodo not know equal!?" (Qur'an 39:9)What we tend nowadays to call "science" in the MITOW or strict sensecove= the latest developments and discoveries in the mathematical,physical, and biological sciences. Yet the expression continues to be usedin a wider sense, one that covers our contemporary social sciences andoccasionally human Sciences (including perhaps the science of religion)as well. If, when speaking of the Islamic perspective on, or conception of,religious belief, scientific belief, and the relation between them, we meanto'address the entire Islamic tradition, we will invariably be faced withan impossible task. To do this successfully, we would have to start fromthe Qur'an and go through Islamic history century by century, if notgeneration by generation, and see how the Qur'anic perspective wasrealized by the Muslim community in diverse regions and disciplines.This process would reveal what tensions and conflicts arose, how thesewere resolved, and what happened when the Muslim world was facedwith the adoption of what we now call "science."Putting this task aside, we can perhaps touch on a few points in thatlong and complex history. First of all, we will speak briefly of theQur'anic perspective and then say a few words about how the differentsciences, when developed, were organized into a general scheme ofhuman knowledge and how this organization implies a certain view of therelation between religious belief and scientific belief. This talk willconclude with the raising of some questions regarding what we understandby the term "Islamic science" when we use it as a historical orclassificatory notion.The Qur'anic PerspectiveThe Arabic expressions in the Qur'an that are used to signify mentaldiscipline and usually translated into English as "science" are primarilytwo: 'ilm, normally rendered as "science" or "knowledge" (a faculty ofsciences is regularly called kulhyat al 'ulum in Arabic, 'ulum being theplural of 'ilm) and &huh, normally tendered as "wisdom." To begin ...